They can't treat you well under abusive supervision: Investigating the impact of job satisfaction and extrinsic motivation on healthcare employees. (November 2021) - Siyal, Saeed; Saeed, Maria; Pahi, Munwar Hussain; Solangi, Rukhman; Xin, Chunlin
Building on the emerging research that has demonstrated the adverse effects of abusive supervision on employee performance, this research draws on the theories of prosocial motivation and action identification. We develop and empirically test a mediation model to examine the indirect impact of abusive supervision on employee performance. Data were obtained from 430 Chinese healthcare employees to validate and test our proposed hypotheses and generalize the findings from Western settings in the Eastern context. The findings indicate that abusive supervision is negatively related to employee performance. Job satisfaction and extrinsic motivation mediated this relationship. The study has some important theoretical and practical implications, and we have also discussed some future directions.